Natural Frequencies of Small Cylinders and Tubes - Peter LISY; Peter Perun (Problemy Mechatroniki, 2015)
The paper deals with modal analysis of the cylinders and tubes and their mutual comparison. Nowadays, modal analysis is a powerful method of describing the vibration properties. When we know own shapes and natural frequencies, we can predict e.g. behaviour of tubes under loading conditions. The tubes dimensions were taken as dimensions which are close to assault rifle barrels. The same dimensions were taken for cylinders. The cylinders and tubes as 3D objects were modelled and their lengths and thicknesses were modified. Modal analysis was performed by LS-DYNA software using FEM with iterative Lanczos method. In Tables 1-12, the natural frequencies for these cantilever beams and their corresponding own shapes with modification in fixing length for three different thicknesses are listed. In Figure 2 and 7-9, these natural frequencies versus modification in fixing length for three different thicknesses for corresponding modes are shown. In Figure 3-5 and 10-12, natural frequencies versus length of cylinders and tubes for three different thicknesses for corresponding modes are shown.